Moisturizing Treatment Outcomes: A Comparative Study of Diabetic and Nondiabetic Skin, Associated With the Presence or Absence of Dermatoporosis - Pinto, Juliana Rodrigues; Silva, Silas Arandas Monteiro e; Leonardi, Gislaine Ricci (Dermatological reviews, 2025)
ABSTRACT Background Skin disorders are highly common in type 1 and 2 diabetes mellitus patients. This study assessed the effects of a moisturizing formulation on photoprotected (volar forearm) and photoexposed (dorsal hand) skin in diabetic and nondiabetic participants, with or without stage I dermatoporosis, comparing it to a reference product. Methods Thirty participants, aged 61–81 years, were included and equally divided into diabetic and nondiabetic groups. Biophysical assessments, including capacitance (hydration), transepidermal water loss (TEWL) measurements, and skin micro‐imaging for roughness evaluation, were performed at baseline, 45, and 60 days. Results The test formulation significantly increased skin hydration, up to 34% on the forearm (FO) and 35% on the dorsal hand (DH) in diabetic participants, and up to 21% on the FO and 27% on the DH in nondiabetic participants. TEWL reduction, indicating improved barrier function, was more pronounced in diabetics (8% on FO and DH), while non‐diabetics showed a 1% reduction on the FO. Skin roughness decreased more in diabetics (16% on FO and 18% on DH) than in non‐diabetics (11% on DH). Diabetic participants showed greater improvements overall. The test formulation and the reference product demonstrated similar effects in improving skin condition. Participants with stage I dermatoporosis showed significant improvements in skin condition, with the test formulation providing greater benefits for diabetics. Conclusion The test formulation effectively enhanced skin hydration and barrier function while reducing skin roughness in diabetic and nondiabetic subjects, regardless of dermatoporosis diagnosis. These findings offer valuable guidance for developing targeted skincare treatments.